Electrochemical Characteristics of Shewanella loihica PV-4 on Reticulated Vitreous Carbon (RVC) with Different Potentials Applied - Wang, Shixin; Zhang, Xiaoming; Marsili, Enrico (Molecules (Basel, Switzerland), 2022)
The current output of an anodic bioelectrochemical system (BES) depends upon the extracellular electron transfer (EET) rate from electricigens to the electrodes. Thus, investigation of EET mechanisms between electricigens and solid electrodes is essential. Here, reticulated vitreous carbon (RVC) electrodes are used to increase the surface available for biofilm formation of the known electricigen Shewanella loihica PV-4, which is limited in conventional flat electrodes. S. loihica PV-4 utilizes flavin-mediated EET at potential lower than the outer membrane cytochromes (OMC), while at higher potential, both direct electron transfer (DET) and mediated electron transfer (MET) contribute to the current output. Results show that high electrode potential favors cell attachment on RVC, which enhances the current output. DET is the prevailing mechanism in early biofilm, while the contribution of MET to current output increased as the biofilm matured. Electrochemical analysis under starvation shows that the mediators could be confined in the biofilm. The morphology of biofilm shows bacteria distributed on the top layer of honeycomb structures, preferentially on the flat areas. This study provides insights into the EET pathways of S. loihica PV-4 on porous RVC electrodes at different biofilm ages and different set potential, which is important for the design of real-world BES.